2008
DOI: 10.1021/jp8065426
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetry in Weakly Supported Media: The Stripping of Thallium from a Hemispherical Amalgam Drop. Theory and Experiment

Abstract: A theoretical model for electrochemical processes in resistive media is applied to interpret the current measured for the stripping of thallium from a Tl/Hg amalgam. Chronoamperometry is presented for a potential step experiment at a 12.5 µm radius hemispherical mercury drop in which thallium is first deposited and then stripped. Unusual features are observed in the transient stripping current, and it is proposed that these occur when the concentration of thallium(I) cations in solution is so great that the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 40 publications
(71 reference statements)
5
44
0
Order By: Relevance
“…The similarity of the sluggish stripping of Zn and Cd at comparable high concentrations also lends support to the origin of acb in electroneutrality. This explanation for the sluggish stripping (observation 3) matches theoretical and experimental results (on Tl) recently published [16,17] and could also imply that the potential relevant for the Nernstian equilibrium be different from the nominal applied potential. However, this mechanism of low medium conductivity cannot explain (at least straightforwardly) the current enhancement of observation 4 (for Zn) or why longer deposition times reduce them (observation 5) given that, for the stripping stage, we impose diffusion limited conditions inside the amalgam where migration cannot have any effect on Zn°t ransport.…”
Section: Tentative Interpretationssupporting
confidence: 88%
See 1 more Smart Citation
“…The similarity of the sluggish stripping of Zn and Cd at comparable high concentrations also lends support to the origin of acb in electroneutrality. This explanation for the sluggish stripping (observation 3) matches theoretical and experimental results (on Tl) recently published [16,17] and could also imply that the potential relevant for the Nernstian equilibrium be different from the nominal applied potential. However, this mechanism of low medium conductivity cannot explain (at least straightforwardly) the current enhancement of observation 4 (for Zn) or why longer deposition times reduce them (observation 5) given that, for the stripping stage, we impose diffusion limited conditions inside the amalgam where migration cannot have any effect on Zn°t ransport.…”
Section: Tentative Interpretationssupporting
confidence: 88%
“…Moreover, a long tradition of literature [12][13][14][15] has pointed out that there might be ''kinetic" problems: even at reduced metal concentration globally lower than the solubility limit, during the deposition there might be spots (in the amalgam, close to the surface of the interphase) where the local concentration exceeds the solubility limit and forms deposits. More recently, experimental and theoretical evidences (with Tl) indicate that the stripping currents are strongly influenced by low supporting electrolyte concentrations [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The additional species in their work are sometimes neutral [71,72] and sometimes charged [66,70], depending on the reaction being modeled. Modeling of uncharged and supporting ionic species has also been a feature of other models in the literature [58][59][60].…”
Section: Historical Reviewmentioning
confidence: 99%
“…Rather, the assumption of a negligibly small electrical double layer is adopted (see below) which offers computational accuracy and simplicity as well as physical insight. In previous papers we have shown that this approach can be used quantitatively to simulated chronoamperometry for a variety of systems [4][5][6][7]. However, most electrochemists use cyclic voltammetry rather than chronoamperometry and so, in this paper, we demonstrate that cyclic voltammetry of the reduction of the cobaltocenium cation in acet onitrile solution:…”
Section: Introductionmentioning
confidence: 77%
“…Also, complexation of the redox species of interest with the added electrolyte can occur, while for the case of many non-polar solvents it is impossible to dissolve the required levels of supporting electrolyte needed for rigorous elimination of migrational effects. For these reasons we have recently developed theoretical and simulation procedures aimed at permitting the quantitative prediction of voltammetry at micro and macroelectrodes (but not nanoelectrodes) under weakly supported conditions [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%